2019
DOI: 10.3389/fpls.2019.00730
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Leaf Reflectance as Proxy for Photosynthetic Capacities: An Ensemble Approach Based on Multiple Machine Learning Algorithms

Abstract: Global agriculture production is challenged by increasing demands from rising population and a changing climate, which may be alleviated through development of genetically improved crop cultivars. Research into increasing photosynthetic energy conversion efficiency has proposed many strategies to improve production but have yet to yield real-world solutions, largely because of a phenotyping bottleneck. Partial least squares regression (PLSR) is a statistical technique that is increasingly used to relate hypers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 80 publications
10
93
0
Order By: Relevance
“…This study provided direct evidence that mapping V cmax and J max at the canopy level could be successful with reflectance spectra (or derived variables) from 400 to 900 nm used as predictors. The findings shown in Figure were in agreement with previous studies to show the PLSR model as an effective tool to predict photosynthetic variables across different spatial scales (Ainsworth et al, ; Dechant et al, ; Fu et al, ; Meacham‐Hensold et al, ; Serbin et al, ; Serbin et al, ). However, this study only used reflectance spectra from 400 to 900 nm for the PLSR modelling, which exhibited an even higher or at least similar R 2 value compared with previous modelling results at the leaf level (e.g., Dechant et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This study provided direct evidence that mapping V cmax and J max at the canopy level could be successful with reflectance spectra (or derived variables) from 400 to 900 nm used as predictors. The findings shown in Figure were in agreement with previous studies to show the PLSR model as an effective tool to predict photosynthetic variables across different spatial scales (Ainsworth et al, ; Dechant et al, ; Fu et al, ; Meacham‐Hensold et al, ; Serbin et al, ; Serbin et al, ). However, this study only used reflectance spectra from 400 to 900 nm for the PLSR modelling, which exhibited an even higher or at least similar R 2 value compared with previous modelling results at the leaf level (e.g., Dechant et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Results presented in this study showed that V cmax and J max could be well estimated for 11 cultivars of one crop (including both genetically modified and wild types) using the proposed three approaches (i.e., PLSR of reflectance spectra, spectral indices, and RTM‐inversion of crop traits) with R 2 all larger than 0.6. These modelling performances at the canopy level using reflectance spectra from 400 to 900 nm were even better than those at the leaf level using a similar dataset from the whole spectrum (400–2,500 nm; Fu et al, ; Meacham‐Hensold et al, ). A similar finding was also observed in comparisons between Serbin et al () and Serbin et al () for tree species: V cmax were better predicted at the canopy level ( R 2 = 0.94) than at the leaf level ( R 2 = 0.89).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations